Effectiveness of renewable energy subsidies in a CO2 intensive electricity system - Aimilia Pattakou; Aryestis Vlahakis (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
Can subsidies to renewable energy effectively internalise CO2 costs in electricity production? Under current policy design it only matters that the replaced energy is dirty, but not how dirty it is. We use a modified peak-load pricing model, including variable renewable generators and the external costs of carbon, to examine the way in which a unit subsidy to variable renewables cannot restore first best optimum. In our model, electricity is generated using a combination of three technology types: two dispatchable, thermal, and CO2 emitting technologies, differing in their emission intensity, and a non-dispatchable renewable technology. We show that available wind capacity is never idle, and derive equations determining optimal installed capacities for all technologies. We then describe the mechanism by which a subsidy that does not discriminate between dirty energies fails to restore first best. Our analysis highlights the importance of a carbon price: even one below the social cost of carbon could have a corrective effect on the merit order of fossil fuels and improve the effectiveness of a subsidy.
Keywords: Q42; Q48; H23; 330; Energy policy; Renewable energy; Environmental subsidy